New Method To Prevent Contamination In Minimal Invasive Surgery: Usage Of Endoprotector - Betül Güzelyüz; Server Sezgin Uludağ; Engin Hatipoğlu; Egemen Özdemir; Sefa Ergün; Kemal Selçuk Şengün (Gazi Medical Journal)
Objective: To reveal the use of a material called endoprotector designed to prevent contamination in minimally invasive abdominopelvic surgery. Methods: Endoprotector is formed by giving a circular shape to the transparent polyurethane material and passing around it in the form of a pürse-string with a surgical suture. This material, which is used in minimally invasive surgeries by inserting it into the abdomen through a trocar hole and laying it on the floor of the operating area, has been in the patent process. Results: It is characteristic that it is a new product, called endoprotector, and the use of a laparoscopic protective drape is a new technique. At the end of the procedure, the extension of the suture shrinks by pulling from the trocar, and the formed pouch is taken out of the abdomen together with the trocar. Difficulty in removing the trocar from within is the only known shortcoming of the technique. Conclusion: Endoprotector is designed to prevent contamination in minimally invasive surgery. It reduces peritonitis and intra-abdominal infections, the need for irrigation, and the use of drains, thus shortening postoperative ileus and hospital stay; and predicted to reduce outcomes such as tumor implantation.